The effectiveness of Pennsylvania resilience training to decrease marital boredom and increase religious commitment and individual resilience - Aghamohammadian-Sharbaf, Hamidreza; Seyedzadeh-Dalooyi, Seyed Iman; Farrokhi, Hossein; Bahri, Faezeh; Mostafapour, Vahid (Chronic Diseases Journal, 2020)
BACKGROUND: Chronic illness is a long-term disease that causes a body structure damage and body functions, and it necessitates changes in the patient's normal life. Resiliency is one of the factors contributing to the development of chronic physical and psychological disorders, which affect marital satisfaction and boredom. Therefore, the aim of this study was to investigate the effectiveness of the Penn Resiliency Program (PRP) on marital boredom, religious commitment, and individual resilience. METHODS: This quasi-experimental research was conducted with a pretest-posttest design and control group. The study population consisted of all married female students of Ferdowsi University of Mashhad, Iran, who had referred to the university clinic in the first 6 months of 2017. The sample consisted of 40 women selected using convenience sampling. They were randomly assigned to experimental and control groups. To collect the required data, the Couple Burnout Measure (CBM) (Pines), Religious Commitment Inventory (RCI) (Worthington et al.), and Connor-Davidson Resilience Scale (CD-RISC) were used. The collected data were analyzed using analysis of covariance (ANCOVA). RESULTS: The results of ANCOVA showed that PRP reduced marital boredom and increased religious commitment and individual resilience in the participants (P < 0.010). CONCLUSION: It can be concluded that the PRP is effective on marital boredom, religious commitment, and individual resilience.